A Guide to Improving the Care of Patients with Fragility Fractures, Edition 2. (June 2015) - Mears, Simon C.; Kates, Stephen L.
Over the past 4 decades, much has been learned about the pathophysiology and treatment of osteoporosis, the prevention of fragility fractures, and the perioperative management of patients who have these debilitating injuries. However, the volume of published literature on this topic is staggering and far too voluminous for any clinician to review and synthesize by him or herself. This manuscript thoroughly summarizes the latest research on fragility fractures and provides the reader with valuable strategies to optimize the prevention and management of these devastating injuries. The information contained in this article will prove invaluable to any health care provider or health system administrator who is involved in the prevention and management of fragility hip fractures. As providers begin to gain a better understanding of the principles espoused in this article, it is our hope that they will be able to use this information to optimize the care they provide for elderly patients who are at risk of or who have osteoporotic fractures.